The application of meta heuristic global optimization algorithms to scheduling problems within the brewing industry - Nash, Graham (My University, 2008)
In this thesis we have presented a mathematical model of a scheduling problem which arises in the Brewing Industry. We have implemented two different types of global optimization algorithms to find the global minimum of the problem. Several instances of the scheduling problem are considered and the results thereof are presented. The results show that significant savings can be made if the global optimization techniques are used in brewery Industry.
Keywords: Simulated Annealing; Tabu Search; Flexible Flow Shop Problem; Brewery Scheduling